Hormone-dependent regulation of GABAA receptor gamma subunit mRNAs in sexually dimorphic regions of the rat brain. - Clark, A S (1998)
Transmission mediated by gamma-aminobutyric acid type A (GABAA) receptors expressed within the medial preoptic area (mPOA) and the ventromedial nucleus (VMN) of the hypothalamus is known to play critical, but contrasting, roles in regulating steroid-dependent sexual behaviours in rats. Previous studies have demonstrated a striking dichotomy in receptor composition between the two regions with regard to gamma, but not alpha or beta, subunit expression. To test if gonadal steroids regulate the expression of the gamma subunit genes within the mPOA and the VMN, in situ hybridization analysis for messenger RNAs encoding the gamma 1, gamma 2Short (gamma 2S) and gamma 2Long (gamma 2L) subunits was done in gonadectomized male and female rats and in gonadally intact females over the oestrous cycle. No significant differences in the expression of the gamma subunit mRNAs were observed in gonadectomized male versus female rats. Significant effects of gonadal state in female rats were observed for gamma 1 mRNA levels in the mPOA and gamma 2L levels in the VMN. These data demonstrate that gonadal hormones exert activational control of expression of GABAA receptor gamma subunit mRNAs and suggest that differences in receptor structure may contribute to the functional modulation of female sexual behaviours mediated by GABAergic transmission in these regions.